Surface characterization, electrochromic and capacitive properties of poly(N-(4-(4-thieno[3, 2-b]thiophen-3-yl-phenyl)phenyl)-N-phenylbenzenamine) film. (17th November 2020) - Topal, Sebahat; Sezer, Esma; Eroglu, Mehmet S.; Ozturk, Turan
Abstract: N -(4-(4-thieno [3, 2- b ]thiophen-3-yl-phenyl)phenyl)- N -phenylbenzenamine (TTpTPA ), synthesized by Suzuki cross-coupling reaction, was electropolymerized in DCM/CAN (4/1 v/v) mixture, containing 0.1 M Bu4 NPF6 . Charge storage property of the polymer, investigated by electrochemical impedance spectroscopy measurements at different potentials, suggested that the highest capacitance value could be obtained at its anodic peak potentials. Double layer and low-frequency capacitances were found to be CDL  = 369 Fg -1 and CLF  = 447 Fg -1 at EDC  = 1.23 V. These values are in good agreement with the results obtained from equivalent circuit model. Electrochromic properties of the corresponding polymer, PolyTTpTPA, were investigated by spectroelectrochemical measurements, which indicated that while the polymer had a gold-orange color in its neutral state with an absorption maximum of 378 nm, it became blue in its oxidized state with an absorption maximum of 850 nm. Chronocoulometric measurement of the film exhibited a residence time of 10 s, indicating a fast response time and stable photoelectrochemical behavior, which are the most important parameters for electrochromic applications. In addition, hydrophobic property of the film, having a contact angle measurement of 115°, is a good advantage for electronic applications for outdoor and wet areas. This work demonstrates that reversible capacitive current property and porous structure of PolyTTpTPA, supported by SEM and AFM images, make it a good candidate for electrochromic and capacitor devices. Highlights: Synthesis of a new monomer based on Thienothiophene and triphenylamine and its electropolymer film was obtained. A high contact angle of 117. A high capacitance of 447.